Effect of Phenolic Levels on the Activity of Bacteria Propionibacterium Acnes in Cassava Extract Ointment Preparations Manihot Esculenta - Nor Zaila; Tutik Tutik; Vito Zhafran Octonaris (Jurnal EduHealth, 2026)
Cassava peel is an abundant agricultural by-product that contains bioactive secondary metabolites with potential pharmaceutical applications. This study aimed to evaluate the effect of phenolic content on the antibacterial activity of cassava peel extract formulated as a topical ointment against Propionibacterium acnes. Cassava peel was extracted using maceration with 96% ethanol and formulated into ointments at three extract concentrations, namely 2% (FI), 4% (FII), and 6% (FIII). Phenolic content was determined using the Folin–Ciocalteu method with UV–Vis spectrophotometry, while antibacterial activity was assessed using the agar well diffusion method. The extraction process produced a yield of 12.52% and phytochemical screening confirmed the presence of flavonoids, saponins, tannins, and phenolic compounds. Phenolic content increased with extract concentration, with values of 0.74 ± 0.04 mg GAE/g for FI, 1.15 ± 0.14 mg GAE/g for FII, and 1.36 ± 0.08 mg GAE/g for FIII. All ointment formulations met physical quality requirements, including homogeneity, acceptable pH range, spreadability, adhesion, and consistent organoleptic properties. Antibacterial testing showed that all formulations exhibited strong inhibitory activity against Propionibacterium acnes. The largest inhibition zone was observed in FI at 16.33 ± 2.56 mm, followed by FII at 12.00 ± 1.81 mm and FIII at 11.50 ± 2.64 mm. The negative control showed no antibacterial activity, confirming that inhibition was attributed to the cassava peel extract. Statistical analysis indicated a significant effect of phenolic content on antibacterial activity (p < 0.05). These findings demonstrate that cassava peel extract ointment has strong antibacterial potential against Propionibacterium acnes, and that antibacterial effectiveness is influenced not only by phenolic content but also by formulation characteristics affecting compound diffusion. The ointment shows promise as a natural topical antibacterial candidate for acne treatment.